Research handbook on the law of treaties - Tams, Christian J.; Tzanakopoulos, Antonios; Zimmermann, Andreas (Edward Elgar Publishing Ltd., 2014)
Offering a conceptual approach to the law of treaties, this insightful book not only sets out the foundational issues but identifies tensions within the field, including formalism vs flexibility, integrity vs flexibility, and uniformity vs specialisation, to name a few... --